Analysis of vector space content for developing a Prezi-integrated linear algebra module: Enhancing elementary algebra learning - Meiva Marthaulina Lestari Siahaan; Fitriani Fitriani; Siska Nopa Br. Tambunan (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
The research aims to analyze vector content material and produce teaching materials that are valid, practical, and effective. The research method used is Alessi and Trollip's development research, which consists of three stages: planning, design, and development. The results of this research indicate that the vector space materials developed for teaching include vectors in R2, R3, and Rn, line and plane parameter equations, dot products and cross products, as well as line and plane coordinate equations in R3. The module assessment from two material experts was 3.33, indicating it is very feasible, while from two media experts it was 3.9625, also indicating it is very feasible. The benefits of this product in supporting students' understanding of vector space material include the composition of the material being based on an in-depth analysis of the textbooks used, relevant sources, and student test results from the previous three years. This approach helps students comprehend vector space, as the module presents relevant images to support the explanations. Additionally, the material in the module is integrated with Prezi, which helps to capture students' interest and encourages them to focus on the explanations. In conclusion, the developed teaching materials are effective in enhancing students' understanding of vector space concepts and are highly feasible for use in educational settings.